The Current Status of Neural Grafting in the Treatment of Huntington’s Disease. A Review - Barker, Roger A. (Frontiers in Integrative Neuroscience, 2011)
Huntington’s disease (HD) is a devastating, fatal, autosomal dominant condition in which the abnormal gene codes for a mutant form of huntingtin that causes widespread neuronal dysfunction and death. This leads to a clinical presentation, typically in midlife, with a combination of motor, psychiatric, cognitive, metabolic and sleep abnormalities, for which there are some effective symptomatic therapies that can produce some transient benefits. The disease, though, runs a progressive course over a 20 year period ultimately leading to death, and there are currently no proven disease modifying therapies. However whilst the neuronal dysfunction and loss affects much of the central nervous system (CNS), the striatum is affected early on in the disease and is one of the areas most affected by the pathogenic process. As a result the prospect of treating HD using neural transplants of striatal tissue has been explored and to date the clinical data is inconclusive. In this review we discuss the rationale for treating HD using this approach, before discussing the clinical trial data and what we have learnt to date using this therapeutic strategy